Experience of Artificial Intelligence in Architectural Space Production within the Scope of Creating "Brand Identity" for a Local Brand - Ekici, Muhlis Arda; Çelik, Tuğçe (Journal of Intelligent Decision Making and Information Science, 2025)
Branding and brand identity emerged from the desire to stand out in line with consumption needs. Branding and corporate identity design are processes that must be carried out simultaneously. In this context, the design of the brand’s structure, interior spaces, and stores intersects with the discipline of architecture in the creation of a "brand identity." Spatial design, through the use of architectural elements and spatial configurations, differentiates the brand and aims to capture customer attention. Today, the role of artificial intelligence (AI) in the design process is being questioned. Text-to-image AI algorithms redefine architectural formation by generating unique and diverse design outputs. In this context, the question, "Can artificial intelligence produce architectural spaces for brand identity?" forms the basis of this research. The study aims to use text-to-image technology to rapidly generate diverse design alternatives for a local brand. The relationship between text to-image technology and decision-making is shaped by its ability to guide and optimize users’ creative processes. This technology allows users to provide text-based inputs to generate visual outputs, playing a critical role in visualizing both design options and possibilities in the decision-making process. By examining the contributions of the generated visuals to brand identity and architectural design, this method is proposed as a new approach to architectural design. While designers assume the role of decision-makers in this process, AI emerges as a significant design parameter.